Service Manual Creation to Develop the Service System in the Faculty of Management. - Intapat, Lukkana (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The research ‘Service Manual Creation to Develop the Service System in the Faculty of Management, Nakhon Pathom Ratchaphat University’ aimed to study the users’ satisfaction with service and to create a service manual of the Faculty of Management, Nakhon Pathom Ratchaphat University. The questionnaires about users’ satisfaction with correspondence service of the Faculty of Management were used for the data collection. One hundred people were a target group. The study found that the characteristics of the service users satisfied the most were ‘Agility’ and ‘Speed’ respectively. About the users’ opinion in staffs, the most satisfied characteristics were ‘Manners’ and ‘Costume and Personality’ respectively. The most satisfied facilitations were ‘The Arrangement of Place and Equipment’ and ‘Classification’. The factors effecting to the service manual creation were the process to service uncomplicatedly and flexibly, speed, the staffs’ politeness, costumes, personality, the arrangement and of place and facility. The service duration was a factor affecting to the development of the service manual. The duration of service should be appropriately set based on the service workload. Moreover, the discrimination of staffs and cleanness of the service area should be developed. Article history : Received 1 April 2018 Revised 2 May 2018 Accepted 8 May 2018 SIMILARITY INDEX = 1.75